Análise do processo licitatório da prefeitura municipal de Passo Fundo - Del Duca, Fábio Vidal Pinheiro (2015)
The purchasing function is inserted in any business activity, whether in the public or in the private area. In public organizations there is a general rule, for the acquisition of goods and services, the requirement of bidding. However, the bidding processes are not always completed successfully, bringing numerous losses, not only for the public organization, as exceedingly to the dependent citizens of its activities. So, analyze the causes that resulted in completed bidding unsuccessfully, in the City Hall Passo Fundo, was the objective of the work. For this, a research was performed, classified as descriptive, as the goal, and qualitative on the approach. Once defined categories of analysis, the data collection through bibliographic research, documentary research and interview. The results indicated that all 329 unsuccessful biddings, corresponding to 19.1% of the total, came on external stage and that approximately 84% were finalized by revocation and the remaining 16% for annulment. In detail, were found twenty-three reasons for the unsuccessful biddings were found, with eight factors accounted for 90% of unsuccessful bidding. For these reasons, twenty-eight proposals for improvements were suggested to reconfigure the acquisition and contracting process, avoiding that the bidding processes are finalized without success. Based on these evidences, the propositions indicate that by increasing the importance and dedication on the internal phase of the bidding stage (planning), more precise will be the descriptions and details of the object, thus making smaller uncertainties in estimates of quantities, deadlines and costs. This would cause public organizations would have increased efficiency in public spending and security in their contracts. Additionally, the possibility of inversion of the phases of bidding, especially in the modalities concorrência and tomada de preços, become real needs for the evolution that the public administration needs.